Uma história pessoal: Os mitos gregos - Pauline Schmitt Pantel (Estado da Arte, 2019)
Sung at festivals in honour of the gods or at banquets, heard in the theatre or in the agora, contemplated in the walls of temples or in table vessels, myths are part of the daily life of the Greeks. Zeus, and the deities of Olympus, Prometheus, Heracles, Oedipus, Theseus, Helen, Pandora, Ulysses are some of them, the most striking. Mythical narratives, whether they are known through texts or through images, participate in the construction of as varied domains of Greek experience as the polytheistic pantheon, food codes, relations between the sexes, the view of the phases of life and death or history communities.